Shamans reconsidered: The Emberá (Chocó) in Darién, Panama (2022)
Introduction: popular religion in Mexico and Central America / Lynn Stephen and James Dow -- Changes in twentieth-century Mesoamerican cargo systems / John K. Chance -- the politics of ritual: the Mexican state and zapotec autonomy, 1926 to 1989 / Lynn Stephen -- The Zincantan cargo waiting lists as a reflection of social, political, and economic changes, 1952-1987 / Frank Cancian -- The political economy of the velas in the Isthmus of Tehuantepec / Leigh Binford -- Sanctity and resistance in closed corporate indigenous communities: coffee money, violence, and ritual organization in chatino communities in Oaxaca / James B. Greenberg -- Appropriating the enemy: highland Maya religions organization and community survival / Duncan M. Earle -- Mission rivalry and conflict in San Blas, Panama / James Howe -- Shamans reconsidered: the Embera (Choco) in Darien, Panama / Stephanie Kane -- Martyrs and virgins: popular religion in Mexico and Nicaragua / Michael James Higgins -- The dynamics of religion in Middle American communities / James Dow and Lynn Stephen.